Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 1298 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Convolvulus siculus L." ] } The dataset includes 1298 records from 67 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002392-150410134957023/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences